Estimation of S-wave Velocity Structures by Using Microtremor Array Measurements for Subsurface Modeling in Jakarta - Ridwan, Mohamad; Afnimar, A.; Widiyantoro, Sri; Irsyam, Masyhur; Yamanaka, Hiroaki (Journal of Mathematical and Fundamental Sciences, 2014)
Jakarta is located on a thick sedimentary layer that potentially has a very high seismic wave amplification. However, the available information concerning the subsurface model and bedrock depth is insufficient for a seismic hazard analysis. In this study, a microtremor array method was applied to estimate the geometry and S-wave velocity of the sedimentary layer. The spatial autocorrelation (SPAC) method was applied to estimate the dispersion curve, while the S-wave velocity was estimated using a genetic algorithm approach. The analysis of the 1D and 2D S-wave velocity profiles shows that along a north-south line, the sedimentary layer is thicker towards the north. It has a positive correlation with a geological cross section derived from a borehole down to a depth of about 300 m. The SPT data from the BMKG site were used to verify the 1D S-wave velocity profile. They show a good agreement. The microtremor analysis reached the engineering bedrock in a range from 359 to 608 m as depicted by a cross section in the north-south direction. The site class was also estimated at each site, based on the average S-wave velocity until 30 m depth. The sites UI to ISTN belong to class D (medium soil), while BMKG and ANCL belong to class E (soft soil).